Immune exposure: how macrophages interact with the nucleus pulposus - Feng, Peng; Che, Ying; Gao, Chunyu; Zhu, Liguo; Gao, Jinghua; Vo, Nam V. (Frontiers in Immunology, 2023)
Intervertebral disc degeneration (IDD) is a primary contributor to low back pain. Immune cells play an extremely important role in modulating the progression of IDD by interacting with disc nucleus pulposus (NP) cells and extracellular matrix (ECM). Encased within the annulus fibrosus, healthy NP is an avascular and immune privileged tissue that does not normally interact with macrophages. However, under pathological conditions in which neovascularization is established in the damaged disc, NP establishes extensive cross-talk with macrophages leading to different outcomes depending on the different microenvironmental stimuli. M1 macrophages is a class of immune cells predominantly pro-inflammatory that promote inflammation and ECM degradation in the NP, creating a vicious cycle of matrix catabolism that drives IDD. In contrast, NP cells interacting with M2 macrophages promote disc tissue ECM remodeling and repair as M2 macrophages are primarily involved in anti-inflammatory cellular responses. Hence, depending on the cross-talk between NP and the type of immune cells (M1 vs. M2), the overall effects on IDD could be detrimental or regenerative. Drug or surgical treatment of IDD can modulate this cross-talk and hence the different treatment outcome. This review comprehensively summarizes the interaction between macrophages and NP, aiming to highlight the important role of immunology in disc degeneration.